Impacts of palmyrah (Borassus flabellifer) fruit pulp-enriched diets on growth and colouration of swordtail (Xipophorus helleri) and platyfish (Xipophorus maculatus) - Sutharshiny Sathyaruban; Deepthi Inoka Uluwadugae; Sivashanthini Kuganathan (Journal of Fisheries, 2025)
The ornamental fish industry urgently needs natural carotenoid sources due to the undesirable effects of synthetic additives. This study examines the effects of an untapped carotenoid source, palmyrah fruit pulp (PFP), on the growth and skin colour of swordtails (Xipophorus helleri) and platies (Xipophorus maculatus). Experimental diets containing 40% crude protein were formulated with varying PFP levels (%) at 0, 3, 6, and 8. A commercial diet was used as a positive control, while a diet without PFP was a negative control. Four-week-old swordtails (n=450) and platies (n=450) were divided into 15 groups for five treatments, and all were kept under the same conditions. The experiment lasted 81 days for the swordtail and 83 days for the platy. The findings show that the 8% PFP diet led to a significant increase in the skin colour in both fish compared to the other treatments. Higher growth performance (ANOVA: p<0.001) was observed in both fish when fed 3, 6, and 8% PFP diets compared to the negative control group; however, no significant difference from the positive control group. All treated groups had a survival rate of over 92%, and weight gains followed strong polynomial relationships (R2>0.98). The study concludes that an 8% PFP-enriched diet effectively influenced skin colour, with TCC levels of 85.59 µg g–1 in swordtails and 80.54 µg g–1 in platies. Furthermore, this diet promotes the growth of swordtails and platies. This diet serves as an adequate substitute for commercial fish feeds in the ornamental fish industry.